Crise ambiental, acumulação e subsistência rural: extractivismo e a nova fronteira de acumulação no contexto de mudanças climáticas - Bruna, Natacha (Desafios para Moçambique 2022, 2022)
A economia moçambicana apresenta uma estrutura típica de uma economia onde o extractivismo predomina em múltiplos sectores. A política económica, em Moçambique, tem centrado-se em promover elevados níveis de Investimento Directo Estrangeiro (IDE), tendo atingido um máximo, em 2013, de cerca de USD 6,697 mil milhões; este montante foi principalmente canalizado para a extensão da capacidade produtiva dos IDEs e da capacidade de escoamento de mercadorias para exportação (Banco de Moçambique, 2019). É deste modo que o capital extractivo exerce a sua influência no crescimento económico no País. Portanto, a grande aposta é principalmente IDE, de média e larga escala, virado para a extracção de recursos naturais e exportação para mercados internacionais, os quais engajam num esquema de extrair-escoar-e-exportar, como é o caso da Vale Moçambique, Kenmare, SASOL, e muitos mais. Está claro que este modelo de crescimento económico não tem sido eficiente e eficaz em reduzir a pobreza e em providenciar uma base produtiva, económica e social para um desenvolvimento sustentável, pelo contrário, tem resultado em altos níveis de dependência do País em recursos externos com altos custos sociais (Castel-Branco, 2014; Mosca et al., 2013). Como resultado, Moçambique é considerado ainda um dos países mais pobres, com cerca de 46% da população a viver abaixo da linha da pobreza (Ministério da Economia e Finanças (MEF), 2016). Os níveis de insegurança alimentar continuam elevados, com cerca de 24% dos agregados familiares do total da população (Secretariado Técnico de Segurança Alimentar e Nutricional (SETSAN), 2014). O cenário de pobreza e vulnerabilidade social é mais intensificado nas zonas rurais, onde estes grandes volumes de investimentos baseados na terra e extracção de recursos naturais são implementados. Nas últimas décadas, as vulnerabilidades sociais históricas e as resultantes da penetração do capital no meio rural têm sido exacerbadas pela intensificação da crise ambiental global e impactos das mudanças climáticas. O relatório do Intergovernamental Panel for Climate Change (IPCC, 2007) afirma que África é o continente mais vulnerável em relação às mudanças climáticas e que até 2050, 350 a 600 milhões de africanos estarão em risco. Em Moçambique, uma grande preocupação está relacionada com a capacidade da população rural de produzir alimentos para a sua subsistência e para garantir a disponibilidade de alimentos num contexto de sistemas de produção de sequeiro altamente dependente de chuvas. Devido à variabilidade climática, alteração dos padrões de precipitação e temperatura, prevê-se que a produção de culturas alimentares, como milho, amendoim, mandioca e mapira, decresça consideravelmente (Abbas, 2022; Brito & Holman, 2012; Joala et al., 2019). É neste contexto que instituições financeiras e organizações internacionais apelam por um «mundo inteligente ao clima» (Banco Mundial, 2010; The Food and Agriculture Organization of the United Nations (FAO), 2013; entre outros). Ou seja, de acordo com estas, tornou-se urgente e uma prioridade global mitigar e adaptar às mudanças climáticas através da implementação de políticas e investimentos verdes e sustentáveis, ou seja, «aquelas que melhoram o desenvolvimento, reduzem a vulnerabilidade e financiam a transição para caminhos de crescimento de baixo carbono» (Banco Mundial, 2010, p. xx).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; climate change / mudanças climáticas; economic development / desenvolvimento económico

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

Electricity access and social sustainability in Mozambique - Salite, Daniela; Cotton, Matthew; Kirshner, Joshua (Oxford Policy Management, 2020)
The demand for access to electricity in developing countries is rapidly increasing as intergovernmental organisations, national governments, and business leaders recognise the social and economic value of infrastructure investment. The institutions that govern energy investment and planning recognise a ‘trilemma’ of system development: low-carbon energy sources are needed to meet global climate change mitigation goals, while also meeting service reliability demands and energy security measures alongside maintaining service affordability, particularly for residents on the lowest incomes in rural, urban, and peri-urban communities. Integrating traditional, centralised grid networks based upon large-scale generation technologies (in the case of Mozambique, this includes hydropower from the Cahora Bassa Dam) with decentralised off-grid renewables such as solar projects in rural communities is a significant technical and governance challenge. Energy providers are tasked with a social mandate to deliver good quality electricity at an affordable price to consumers while widening access to underserved populations. Providing access to clean and reliable energy sources is embodied in Sustainable Development Goal 7 as one of the preconditions for socioeconomic development, poverty reduction, and human wellbeing (Pueyo and Maestre, 2019; UN Energy, 2005). International development practitioners and policy networks recognise the tangible benefits of electricity as a form of energy service provision. These tangible benefits include lighting and powering appliances at domestic, private, and institutional levels and increased telecommunications coverage, which collectively provide new personal and business development opportunities, healthcare and food safety benefits, and improved leisure and night-time education prospects (UN Energy, 2005). They also minimise the health risks and ecological impacts associated with black-carbon fuels such as charcoal, which diminish air quality within residential buildings (Anenberg, 2017) and lead to deforestation (Sedano et al., 2016). In order to enhance electricity sector performance, many sub-Saharan African countries have implemented significant governance reforms. It is necessary, however, to evaluate whether such reforms facilitate expanded social access to electricity, whether they improve service quality, public utility, and financial stability, and whether they lead to broader social and environmental sustainability goals. In this policy brief, we assess these dimensions related to the case of Mozambique, a country where major progress has been made to increase population-wide access to electricity from around 6% in 2004 (Chambal, 2010) to 32% in 2019 (EDM, 2020a). Though policy progress is significant, challenges remain, particularly in rural areas, where only around 6% of the population have electricity access (EDM, 2018a).
Keywords: G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; ⛔ No DOI found

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

The Price of a Green Conscience - Brown, Jasmine; Ewald, Jonas; Fritz, Heiko (Linneaus University, 2020)
Scholars and civil society organizations have over the last decade referred to large-scale carbon sequestration TPPs as "carbon colonialism" (Carmody and Taylor, 2016) as well as a "development by dispossession" dressed in new clothing behind words such as climate change mitigation and development (Kröger, 2012). Concerns have been raised that the trade-offs from the implementation of industrial tree plantations (ITPs) may result in conflicting effects on countries' overall development (The Oakland Institute, 2019; Osborne, 2015; Nel & Hill, 2013). Moreover, NGO's and think tanks, such as FIAN (2012) and the Oakland Institute (2017, 2019), have released reports in which such tree planting projects are accused of displacing people and violating human rights (FIAN, 2012; The Oakland Institute, 2017, 2019; Carmody & Taylor, 2016). This thesis explores the impacts of carbon forestry projects, emphasizing the impacts of ITPs on local livelihoods and their subsequent effects on development. Three dimensions have been chosen to limit the scope of this thesis: (1) food security; (2) access to land; and (3) employment & income. The thesis is conducted using a qualitative desk study and secondary analysis of two multiple case studies of Uganda and Mozambique. The findings presented suggest carbon forestry projects may negatively affect all three dimensions, ultimately affecting communities' sustainable development. The author recommends further research to evaluate the complex effects of carbon forestry projects.
Keywords: *snowball; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; poverty / pobreza